Strategi Komunikasi Humas Pemerintah Kota Surabaya dalam Melayani dan Menggali Potensi Masyarakat Melalui Media Sosial - Adelia Masrifah Cahyani (Jurnal Ilmu Komunikasi, 2020)
This article discusses how the communication strategy of the Surabaya City Government Public Relations in serving and exploring the potential of the community through social media. This study used a qualitative descriptive method. From the results of this study, four findings were obtained. Firstly, in conveying messages through social media, the Surabaya City Government Public Relations, especially in conducting discussions with the social media team, to determine the market for the message. Secondly, social media content which is so varied according to what is happening in the community, especially in the city of Surabaya. Thirdly, the Public Relations of the Surabaya City Government holds a photo contest on social media every month. It is also a place to facilitate the aspirations and work of the citizens of the city of Surabaya. Fourth, in the use of social media, the Surabaya City Government Public Relations has its own segmentation which aims to make it easier for the public to sort out the information needed through social media